Understanding the Dynamics of Ancillary Pelagic Species in the Adriatic Sea - Angelini, Silvia; Armelloni, Enrico N.; Costantini, Ilaria; De Felice, Andrea; Isajlović, Igor; Leonori, Iole; Manfredi, Chiara; Masnadi, Francesco; Scarcella, Giuseppe; Tičina, Vjekoslav; Santojanni, Alberto (Frontiers in Marine Science, 2021)
The status of fishery resources in the Mediterranean Sea is critical: most of the fish and shellfish stocks are in overexploitation and only half of them result routinely assessed. This manuscript presents the use of Surplus Production Models (SPMs) as a valid option to increase the number of assessed stocks, with a specific attention to the Adriatic basin. Particularly, the stock of European sprat (Sprattus sprattus), Mediterranean horse mackerel (Trachurus mediterraneus) and Atlantic horse mackerel (Trachurus trachurus) living in the Adriatic Sea have been evaluated comparing three SPMs: Catch Maximum Sustainable Yields (CMSY), Stochastic surplus Production model in Continuous Time (SPiCT) and Abundance Maximum Sustainable Yields (AMSY). The different approaches present some variations; however, they generally agree on describing all the stocks close to the reference values for both biomass and fishing mortality in the most recent year. For the European sprat, AMSY results being the most robust model since for this species survey data allow to depict a clearer picture of the history of this stock. Indeed, for the horse mackerel species, CMSY or SPiCT result being the preferred model, since for these species landings are not negligible. Notwithstanding age-structured assessments remain the most powerful approach for evaluating the status of resources, SPMs have proved to be a powerful tool in a data-limited context.